Novel insights into the progression and prognosis of the calpain family members in hepatocellular carcinoma: a comprehensive integrated analysis - Dai, Dongjun; Wu, Dehao; Ni, Runliang; Li, Ping; Tian, Zhifeng; Shui, Yongjie; Hu, Hanguang; Wei, Qichun (Frontiers in Molecular Biosciences, 2023)
The goal of our bioinformatic study was to comprehensively analyzed the association between the whole calpain family members and the progression and prognosis of hepatocellular carcinoma (HCC).The data was collected from The Cancer Genome Atlas (TCGA). The landscape of the gene ex-pression, copy number variation (CNV), mutation and DNA methylation of calpain members were analyzed. The clustering analysis was performed to stratify the calpains related groups. The least absolute shrinkage and selection operator (LASSO) based cox model was used to select hub survival genes.We found 14 out of 16 calpain members expressed differently between tumor and normal tissues of HCC. The clustering analyses revealed high and low risk calpains groups which had prognostic difference. We found the high risk calpains group had higher B cells infiltration and higher expression of immune checkpoint genes HAVCR2, PDCD1 and TIGHT. The CMap analysis found that the histone deacetylases (HDAC) inhibitors trichostatin A and PI3K-AKT-mTOR pathway inhibitors LY-294002 and wortmannin might have therapeutic effect to high risk calpains group. The DEGs between calpains groups were identified. Subsequent univariate Cox analysis of each DEG and LASSO-based Cox model obtained a calpains-related prognostic signature. The risk score model of this signature showed well ability to predict the overall survival of HCC patients in TCGA datasets and external validation datasets from the Gene Expression Omnibus database and Inter-national Cancer Genome Consortium database.We found that calpain members were associated with the progression, prognosis and drug response of HCC. Our results require further studies to confirm.